Pendekatan Psikologi Sastra dalam Pembelajaran Bahasa Arab: Analisis Pemanfaatan Syair Arab sebagai Media Pembelajaran - Muhammad Miftah Fathurrohman; Muhammad Zainur Rofiq; Muhammad Wildan Taufik; Acep Hermawan; Eva Latifah Fauzia (MAN 4 Kota Pekanbaru, 2026)
The approach of literary psychology in learning Arabic is one of the innovative alternatives to create a more humanistic and contextual learning process. This study aims to describe the use of Arabic poetry as a medium for learning Arabic through a literary psychology approach and analyze the psychological values contained in it on students' motivation and emotional involvement. This research uses a descriptive qualitative method with a library research approach. Research data were obtained from Arabic verses, books, journals, and scientific references related to literary psychology and Arabic language learning. Data collection techniques are carried out through documentation and literature studies, while data analysis uses data reduction, data presentation, and descriptive conclusions. Based on the literature analysis, Arabic poetry has great potential as a medium for learning Arabic because it is able to integrate linguistic, aesthetic, emotional, and reflective aspects simultaneously. Psychological values such as motivation, empathy, optimism, patience, and self-reflection contained in Arabic poetry have been proven to increase students’ interest in learning, emotional engagement, and understanding of Arabic materials. Thus, the literary psychology approach can be an alternative to modern Arabic learning that is more communicative, meaningful, and oriented towards the development of students’ character.